Comparing the Effect of AOs and TPS on EFL Learners’ Listening Comprehension - Imam Sudarmaji; Aprianna Simgih (Universitas Tidar, 2022)
Listening Comprehension is the language skills should be developed through listening to children as they grow. Listening Comprehension has been claimed as the most challenging skill to teach since many research found that EFL learners are worried to have a listening class. This research aimed to know whether there is a significant effect of Advance Organizers (AOs) and Think-Pair-Share (TPS) on EFL learners’ listening comprehension. This study is to determine which one is more dominant between Advance Organizers (AOs) and Think-Pair-Share (TPS) to increase EFL learners’ listening comprehension in the Eleventh grade of a senior high school on Tangerang Regency. This research is a quantitative method, with 36 learners as the sample which is taken non-random by using quasi-experimental research time-series design. The data were collected by using the test including pretest and posttest. The results revealed that there was a significant effect used by Advance Organizers and Think-Pair-Share. Therefore, Advance Organizers was more dominant than Think-Pair-Share to increase EFL learners’ listening comprehension.